The Optimal Dispatch of Traffic and Patrol Police Service Platforms - Ke Quan Zhao; Li Luo; Yuan Mei Xia (Journal of Applied Mathematics)
The main goal of this paper is to present a minmax programming model for the optimal dispatch of Traffic and Patrol Police Service Platforms with single traffic congestion. The objective is to minimize the longest time of the dispatch for Traffic and Patrol Police Service Platforms. Some numerical experiments are carried out, and the optimal project is given.